The contribution of mitochondrial function to reproductive aging - Bentov, Yaakov (Springer US, 2011)
PURPOSE: The number of women attempting to conceive between the ages of 36 and 44 has increased significantly in the last decade. While it is well established that women’s reproductive success dramatically declines with age, the underlying physiological changes responsible for this phenomenon are not well understood. With assisted reproductive technologies, it is clear that oocyte quality is a likely cause since women over 40 undergoing in vitro fertilization (IVF) with oocytes donated by younger women have success rates comparable to young patients. Apart from oocyte donation, there is no known intervention to improve the pregnancy outcome of older patients. The aim of this paper was the review the relevant data on the potential role of mitochondria in reproductive aging. METHOD: Review of current literature on the subject. RESULTS: We present the current evidence that associate mitochondrial dysfunction with age related decrease in female reproductive outcome. CONCLUSIONS: The aging process is complex, driven by a multitude of factors thought to modulate cellular and organism life span. Although the factors responsible for diminished oocyte quality remain to be elucidated, the present review focuses on the potential role of impaired mitochondrial function.